Law applicable to armed conflict / Ziv Bohrer, Janina Dill, Helen Duffy. - Bohrer, Ziv; Dill, Janina, 1983-; Duffy, Helen (Law teacher) (Max Planck trialogues on the law of peace and war, 2020)
Which law applies to armed conflict? This book investigates the applicability of international humanitarian law and international human rights law to armed conflict situations. The issue is examined by three scholars whose professional, theoretical, and methodological backgrounds and outlooks differ greatly. These multiple perspectives expose the political factors and intellectual styles that influence scholarly approaches and legal answers, and the unique trialogical format encourages its participants to decenter their perspectives. By focussing on the authors' divergence and disagreement, a richer understanding of the law applicable to armed conflict is achieved. The book, firstly, provides a detailed study of the law applicable to armed conflict situations. Secondly, it explores the regimes' interrelation and the legal techniques for their coordination and prevention of potential norm conflicts. Thirdly, the book moves beyond the positive analysis of the law and probes the normative principles that guide the interpretation, application and development of law.